PEDAGOGICAL CONTENT KNOWLEDGE OF TEACHING ENGLISH TO YOUNG LEARNERS: THE DEGREE OF CONSISTENCY BETWEEN ENGLISH TEACHERS’ PERCEPTIONS AND IMPLEMENTATION - Dewi, Putu Murtiana; Utami, I Gusti Ayu Lokita Purnamika; Utami, Ida Ayu Made Istri (Universitas Pendidikan Ganesha, 2020)
The study aimed at analyzing English teacher perceptions and its implementation of Pedagogical Content Knowledge (PCK) of teaching English for young learners and the comparison between teachers perceptions’ and its implementation by English Primary School in Denpasar. This research used mixed method design with a qualitative dominant. The subjects of this research were three teachers from three different schools in Denpasar who taught English for young learners. Convenience sampling techniques was used in selecting subjects and schools. This research used 4 instruments to get the data, namely: the researcher (2) questionnaire of teachers’ perceptions of pedagogical content knowledge, observation sheet to record teachers’ PCK implementation and (4) interview guide. The result showed the average score of teachers’ perceptions was 3.85 which categorized as high with the interval 3.3335 ≤ M ≤ 4.0005. The average score teachers’ implementation was 8.85 which categorized as low with the interval 7.84 ≤ M ≤ 13.06. In addition, the study found discrepancy between teachers’ perceptions and its implementation. Since the perceptions was in a high category and the implementation was in a low category, this comparison falls in a no consistency category. Such discrepancy caused by the lack of teaching preparation, the uninteresting teaching strategy which included few to no media and the monotonous teaching sources. Teacher professional awareness to do Continuing Professional Development (CPD) for English teachers at primary education needs to be reinforced as an effort of quality assurance.